Hard coat resin composition for molding film for automobile exterior, hard coat film for molding, method for producing insert molded article, insert molded article, and out-mold molded article

By using a hard coat resin composition containing polyurethane acrylate and fluorine-containing organosilicon compounds during the molding process of the automotive exterior, the problem of microcracks on the curved surface of the hard coat resin layer is solved, and high chemical resistance and weather resistance of the automotive exterior molded products are achieved.

CN119562894APending Publication Date: 2025-03-04AICA KOGYO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380053260.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-11
Filing Date
2023-03-14
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

During the forming process of automotive exteriors, the hard coat resin layer is prone to microcracks on the curved surface, resulting in difficulty in forming.

Method used

A hard coat resin composition for forming thin films of automotive exteriors is used, which comprises a polyurethane acrylate, a light stabilizer, a photopolymerization initiator, and a fluorine-containing silicone compound having reactive functional groups. The composition is molded through a mold and molten resin is emitted on opposite sides to form a resin molded product.

Benefits of technology

This technical method can effectively solve the problem of microcracks on the curved surface of the hard coat resin layer, ensuring that the molded product has characteristics suitable for automotive exteriors, such as chemical resistance, weather resistance and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237545080000121
    Figure BDA0005237545080000121
  • Figure BDA0005237545080000131
    Figure BDA0005237545080000131
  • Figure BDA0005237545080000161
    Figure BDA0005237545080000161
Patent Text Reader

Abstract

A hard coat resin composition for a film for molding an automobile exterior, which contains a urethane acrylate (A), a light stabilizer (B), a photopolymerization initiator (C), and a fluorine-containing organosilicon compound having a reactive functional group, and wherein (A) has a diisocyanate generated by reacting an ethylene glycol with an isophorone diisocyanate; and further reacting with pentaerythritol triacrylate to form a structure. The weight average molecular weight of (A) is from 3,500 to 12,000.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This international application claims the priority of Japanese Patent Application No. 2022-110973 filed in the Japan Patent Office on July 11, 2022, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to a hard-coat resin composition for a film for molding of automobile exterior, a hard-coat film for molding, a method for producing an insert-molded article, an insert-molded article, and an out-mold molded article. Background Art

[0004] In recent years, resin molded bodies have been increasingly used for interior and exterior parts of automobiles, exterior parts of information terminals, parts for home appliances, etc., for the purpose of weight reduction. The surface of a resin molded body can be decorated or processed using various methods. Among the methods for decorating or processing the surface of a resin molded body, the method of processing and decorating the outermost surface of a resin molded body using a film can improve the degree of freedom of design compared to the method of using a coating such as spraying, and it is easy to process and decorate a surface with a three-dimensional concave-convex shape. In addition, due to its excellent productivity, it is widely used.

[0005] Insert molding is widely known as a molding method using film. In insert molding, after printing a pattern on the surface of the film, three-dimensional molding is performed in a state where the film is softened by heating, and then the film is set in a mold for injection molding. Especially for interior parts such as car dashboards and consoles, the traditional mainstream water pressure transfer is often rejected due to drainage problems and VOC (volatile organic compounds) problems, and insert molding is introduced as an alternative process. In addition, in recent years, molding methods using films have gradually been introduced in the field of exterior decoration such as the front grille and roof of automobiles. The reason is that in order to adapt to electrification (EV), the demand for lightweight parts has further increased, which has promoted the development of resin parts. At the same time, from an environmental perspective, the use of spraying on resin parts has begun to be avoided.

[0006] In order to improve the surface hardness and scratch resistance, a hard coating resin layer is sometimes provided on a molding film used for insert molding. A molding film provided with a hard coating resin layer is a molding hard coating film. In a molding hard coating film, if the hard coating resin layer is cured, there is a problem that microcracks are generated in the hard coating resin layer on the curved surface when processing into a three-dimensional shape, making molding difficult.

[0007] As a hard coating resin for insert molding, the applicant disclosed a hard coating agent containing a triazine ring-containing (meth)acrylate prepolymer and organic fine particles with an average primary particle size of 80 to 500 nm (see Patent Document 1). When the film thickness of the hard coating agent is 1 to 10 μm, it can have both sufficient flexibility and surface properties.

[0008] In the case of automobile exterior applications, the hard coating film for molding preferably has properties suitable for its application. Suitable properties for automobile exterior applications include, for example, one or more of the following: stable molding in large sizes, chemical resistance, weather resistance sufficient to withstand ultraviolet rays and temperature differences, and durability.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent No. 4848200 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] In one aspect of the present disclosure, a hard coating resin composition for a film for molding of an automobile exterior, a molding hard coating film, a method for producing an insert molded product, an insert molded product, and an out-mold molded product are preferably provided, all of which have properties suitable for automobile exterior use.

[0014] Solutions to the problem

[0015] One embodiment of the present disclosure provides a hard coating resin composition for a film for molding automobile exterior, comprising: polyurethane acrylate (A), a light stabilizer (B), a photopolymerization initiator (C), and a fluorine-containing organosilicon compound having a reactive functional group, wherein (A) has a structure formed by further reacting a diisocyanate generated by the reaction of ethylene glycol and isophorone diisocyanate with pentaerythritol triacrylate, and the weight average molecular weight of (A) is 3,500 to 12,000.

[0016] A hard-coat resin composition for an automobile exterior molding film according to one embodiment of the present disclosure has properties suitable for automobile exterior applications.

[0017] Another aspect of the present disclosure is a method for manufacturing an insert molded product, which uses a molded hard coating film having a substrate and a solidified layer on the substrate to form a resin molded product by molding the film using a mold and injecting molten resin from a side opposite to the solidified layer.

[0018] The cured layer is a cured product of a resin composition, which comprises: polyurethane acrylate (A), a light stabilizer (B), a photopolymerization initiator (C), and a fluorine-containing organosilicon compound having a reactive functional group, wherein the (A) has a structure formed by further reacting a diisocyanate generated by the reaction of ethylene glycol and isophorone diisocyanate with pentaerythritol triacrylate, and the weight average molecular weight of the (A) is 3,500 to 12,000.

[0019] According to a method for producing an insert-molded product according to another aspect of the present disclosure, it is possible to produce an insert-molded product having characteristics suitable for automobile exterior applications. DETAILED DESCRIPTION

[0020] Hereinafter, exemplary embodiments of the present disclosure will be described.

[0021] 1. Hard coating resin composition for film forming of automobile exterior

[0022] The hard-coat resin composition for a film for molding automobile exterior disclosed in the present invention (hereinafter referred to as HC resin composition) comprises: polyurethane acrylate (A), a light stabilizer (B), a photopolymerization initiator (C), and a fluorine-containing organosilicon compound having a reactive functional group, wherein (A) has a structure formed by further reacting a diisocyanate generated by the reaction of ethylene glycol and isophorone diisocyanate (hereinafter referred to as IPDI) with pentaerythritol triacrylate (hereinafter referred to as PETA),

[0023] In addition, in this specification, (meth)acrylate refers to both acrylate and methacrylate. The HC resin composition is used to form a hard coat layer of a molding film. The molding film is used for molding automobile exterior parts.

[0024] IPDI used to synthesize (A) is an alicyclic diisocyanate. IPDI has less yellowing, excellent weathering stability, high rigidity, and can improve the hardness of the cured product of the HC resin composition. By reacting IPDI with ethylene glycol having a very short carbon chain, the concentration of polyurethane bonds in the molecule can be increased, thereby forming a main skeleton of a linear structure having high chemical resistance and high rigidity. When polyethylene glycol is used instead of ethylene glycol, the concentration of polyurethane bonds tends to be low, resulting in reduced chemical resistance.

[0025] The synthesis method of (A) is not particularly limited, and a known synthesis method can be used. The reaction during the synthesis of (A) can be carried out without a solvent, but as the molecular weight of (A) increases, stirring may become difficult, so ketones such as butanone, and aromatic inert solvents such as xylene can also be used to carry out the reaction.

[0026] In addition, it is preferred to use a catalyst for the reaction between ethylene glycol and the hydroxyl group and the isocyanate group of PETA. Examples of the catalyst include tin catalysts such as dibutyltin dilaurate and metal alkoxide catalysts such as cobalt naphthenate. The reaction temperature can be appropriately set, but is preferably 40 to 120°C, and more preferably 60 to 100°C.

[0027] The weight average molecular weight (hereinafter referred to as Mw) of (A) is 3,500 to 12,000, preferably 3,500 to 11,000, more preferably 3,500 to 10,000, particularly preferably 3,500 to 12,000.

[0028] When the Mw of (A) is less than 3,500, the elongation at break of the HC resin composition becomes low, making it difficult to ensure sufficient moldability. When the Mw of (A) exceeds 12,000, the wear resistance of the HC resin composition decreases, and it becomes difficult to adjust the viscosity of the HC resin composition to a viscosity with good processability. The Mw of (A) can be adjusted by adjusting the molar ratio of ethylene glycol to be reacted and IPDI.

[0029] When the molar ratio of IPDI to ethylene glycol is close to 1:1, the Mw of (A) tends to increase. In addition, the Mw of (A) is calculated by measuring the molecular weight converted to standard polystyrene by gel permeation chromatography. In order to measure the Mw of (A), a column filled with styrene divinyl benzene material as a filler and tetrahydrofuran as an eluent was used.

[0030] The amount of (A) added is preferably 55 to 95% by weight, more preferably 65 to 92% by weight, and particularly preferably 70 to 90% by weight relative to the total solid content of the HC resin composition. By setting the amount of (A) added to be 55% by weight or more, sufficient fracture strength and chemical resistance of the HC resin composition can be ensured. By setting the amount of (A) added to be 95% by weight or less, sufficient weather resistance of the HC resin composition can be ensured.

[0031] The light stabilizer (B) used in the present disclosure is formulated to suppress the degradation of the cured film caused by exposure to ultraviolet rays or radiant heat when the HC resin composition is used outdoors. For example, as the light stabilizer (B), (b1), (b2), etc. can be cited. (b1) is a radical scavenger that effectively captures alkyl radicals and peroxy radicals generated by polymers degraded by ultraviolet light. (b2) is an ultraviolet absorber that suppresses the decomposition of polymers by converting absorbed ultraviolet energy into heat energy, etc. It is preferred to use (b1) and (b2) in combination.

[0032] As free radical scavengers (b1) used in the present disclosure, for example, hindered amines (hereinafter referred to as HALS), hindered phenols, aromatic amines, etc. (b1) can be used alone or in combination of two or more. Among them, HALS are preferred because they have high free radical scavenging efficiency even at low concentrations.

[0033] The amount of (b1) is preferably 1 to 10% by weight, more preferably 2 to 8% by weight, and particularly preferably 3 to 6% by weight relative to the total solid content of the HC resin composition. By setting the amount of (b1) within this range, sufficient light stability of the HC resin composition can be ensured. Examples of commercially available HALS include Tinuvin 123 and Tinuvin 249 (trade names, manufactured by BASF Japan).

[0034] The ultraviolet absorber (b2) used in the present disclosure is a free radical chain initiation inhibitor having an absorption band in the high-energy harmful ultraviolet region. By using (b2) and (b1) in combination, the weather resistance of the HC resin composition can be further improved and the weather resistance can be made more stable. As (b2), for example, benzotriazoles, triazines, and benzophenones can be listed. (b2) can be used alone or in combination of two or more. Among them, hydroxyphenyl triazines are preferred because they can strongly absorb the long-wavelength band of ultraviolet rays.

[0035] The amount of (b2) added is preferably 0.3 to 5% by weight, more preferably 0.5 to 3.0% by weight, and particularly preferably 0.6 to 1.5% by weight relative to the total solid content of the HC resin composition. By setting the amount of (b2) added within this range, sufficient ultraviolet absorption properties of the HC resin composition can be ensured. In addition, the amount of the sum of (b1) and (b2) (B) added is preferably 1.0 to 12% by weight, more preferably 1.5 to 10% by weight, and particularly preferably 4.0 to 8.0% by weight relative to the total solid content of the HC resin. By setting the amount of the sum of (b1) and (b2) (B) added to 1.0% by weight or more, it is expected that the weather resistance of the HC resin composition will be improved. By setting the amount of the sum of (b1) and (b2) (B) added to 12% by weight or less, (B) will not be excessively added, and sufficient adhesion between the HC resin composition and the substrate can be ensured. Examples of commercially available products of (b2) include Tinuvin 460 and 477 (trade names, manufactured by BASF Japan).

[0036] The photopolymerization initiator (C) used in the present disclosure generates free radicals when irradiated with ultraviolet rays, electron beams, etc. The generated free radicals initiate a polymerization reaction. As (C), for example, general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide can be used.

[0037] By arbitrarily selecting the light absorption wavelength of the polymerization initiator, curing properties can be imparted in a wide wavelength range from the ultraviolet region to the visible light region. Specifically, as benzyl ketals, there is 2,2-dimethoxy-1,2-diphenylethane-1-one. α As α-hydroxyacetophenones, there are 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propane-1-one. As α-aminoacetophenones, there are 2-methyl-1-(4-methylthiophenyl)-2-morpholinylpropane-1-one. As acylphosphine oxides, there are 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. (C) can be used alone or in combination of two or more.

[0038] Among them, α-hydroxyacetophenones that are not prone to yellowing are preferably included. Commercially available products of α-hydroxyacetophenones include Omnirad 127D, 184 and 2959 (trade names, manufactured by IGM Resins). The amount of (C) is preferably 2 to 12 parts by weight, more preferably 3 to 10 parts by weight, relative to 100 parts by weight of the free radical polymerizable component.

[0039] The HC resin composition disclosed herein can be added with a crosslinking agent, a leveling agent, an adhesion promoter, an antioxidant, a bluing agent, a pigment, a defoaming agent, a thickener, an anti-settling agent, an antistatic agent, an antifogging agent, an antibacterial agent, a wax, a matting agent, a hydrophilic agent, a waterproofing agent, an inorganic filler, an organic fine particle, etc. as needed within a range that does not impair the performance.

[0040] As the crosslinking agent, multifunctional (meth)acrylates are preferably used in view of low viscosity and excellent compatibility with (A). For example, bifunctional (meth)acrylates include (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, and dicyclopentyl diacrylate.

[0041] Examples of the trifunctional (meth)acrylate include trimethylolpropane tri(meth)acrylate and pentaerythritol tri(meth)acrylate.

[0042] Examples of the tetrafunctional (meth)acrylate include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, and diglycerol tetra(meth)acrylate.

[0043] Examples of the pentafunctional (meth)acrylate include dipentaerythritol penta(meth)acrylate.

[0044] As hexafunctional (meth)acrylates, dipentaerythritol hexa(meth)acrylate and the like can be cited. Multifunctional (meth)acrylates can be used alone or in combination of two or more. Among them, dipentaerythritol hexaacrylate (hereinafter referred to as DPHA) is preferred from the viewpoint of good reactivity and difficulty in reducing moldability.

[0045] The amount of the crosslinking agent added is preferably 30 parts by weight or less, more preferably 25 parts by weight or less, relative to 100 parts by weight of (A). By controlling the amount of the crosslinking agent added to 30 parts by weight or less, sufficient moldability of the HC resin composition can be ensured while improving reactivity. In addition, the amount of the crosslinking agent added relative to the total solid content of the HC resin composition is preferably 20% by weight or less, more preferably 10% by weight or less.

[0046] The leveling agent has the function of repairing the defects of the coating film before forming the coating film of the HC resin composition. The reason for repairing the defects of the coating film is as follows. The surface of the coating film of the HC resin composition may have uneven surface tension. The leveling agent balances the surface tension by spreading on the coating film surface in the shape of a thin film. As a result, the defects of the coating film can be repaired.

[0047] As the leveling agent, silicone, fluorine, fluorine-containing organosilicon compounds, acrylic acid, etc. can be cited. Preferably, the leveling agent has a reactive functional group that can polymerize with the binder resin to form a cured coating. In this case, the leveling agent is not easy to fall off over time due to reasons such as seepage in the cured coating, and the effect can be maintained for a long time. As the leveling agent having a reactive functional group that can polymerize with the binder resin to form a cured coating, a fluorine-containing organosilicon compound is preferred.

[0048] The amount of the leveling agent is preferably 0.1 to 3% by weight, more preferably 0.3 to 1% by weight, relative to the total solid content of the HC resin composition. By setting the amount of the leveling agent within this range, sufficient leveling can be ensured when the HC resin composition is applied. Commercially available products of the leveling agent include X-71-1203M (trade name, manufactured by Shin-Etsu Chemical Co., Ltd., an acryl-containing fluorinated organic silicon compound) and the like.

[0049] 2. Hard coating film for molding

[0050] As the substrate for coating the HC resin composition, a composite substrate of a polycarbonate (hereinafter referred to as PC) substrate and an acrylic substrate (hereinafter referred to as PC / acrylic composite substrate) is preferred. PC has excellent impact resistance and high heat resistance. Acrylic substrate has high transparency and high hardness.

[0051] Here, the PC / acrylic composite substrate is, for example, a resin laminate having an acrylic resin layer on at least one surface of a PC resin layer. The PC resin and the acrylic resin are preferably laminated by co-extrusion molding.

[0052] For PC / acrylic composite substrate, the acceptance strength is 0.55W / m at 60°C 2 The ΔE before and after 100 hours of UVB light irradiation is preferably 1.0 or less, more preferably 0.8 or less, and particularly preferably 0.5 or less. When ΔE exceeds 1.0, the damage to the decorative layer caused by the transmitted ultraviolet rays will increase significantly. In particular, when red or blue colors with poor UV resistance are used in the decorative layer, obvious discoloration is more likely to occur over time.

[0053] When the HC resin composition is applied to a substrate, the HC resin composition may be diluted with a solvent to improve coating properties. Examples of the solvent include alcohol solvents such as ethanol, n-propanol, isopropanol, n-butanol, isobutanol, and diacetone alcohol; ketone solvents such as acetone, methyl ethyl ketone (hereinafter referred to as MEK), methyl isobutyl ketone, and cyclohexanone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as propylene glycol monomethyl ether (hereinafter referred to as PGM), diethyl ether, and diisopropyl ether; hydrocarbon solvents such as cyclohexane and methylcyclohexane; and the like.

[0054] As the solvent, the above solvents may be used alone or in combination of two or more. When diluted with a solvent, the solid content of the diluted HC resin composition is, for example, 10 to 70%, but there is no particular restriction and the solid content may be appropriately set to obtain a viscosity that is easy to apply.

[0055] There is no particular limitation on the method of coating the HC resin composition. As the method of coating the HC resin composition, a known coating method or a known printing method can be used. Examples of known coating methods include spray coating, roller coating, die coating, air knife coating, blade coating, spin coating, reverse coating, gravure coating, wire rod coating, etc. Examples of known printing methods include gravure printing, screen printing, offset printing, inkjet printing, etc. The thickness of the coated film when dried is, for example, 1 μm to 10 μm, but is not limited to this range.

[0056] As the light source of ultraviolet irradiation used when curing the coating of the HC resin composition, there are low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, LED lamps, electrodeless ultraviolet lamps, etc. The atmosphere for irradiating ultraviolet rays can be air or in an inert gas such as nitrogen or argon. In addition, during ultraviolet irradiation, the curing performance of the coating can be further improved by heating the backing roller or using an IR heater to heat the coating. As ultraviolet irradiation conditions, an irradiation intensity of 500mW / cm 2 ~3000mW / cm2, and the exposure amount is 50~400mJ / cm2, but not limited to this range.

[0057] The hard coating film for molding (hereinafter referred to as HC film) obtained by coating and curing the HC resin composition on a substrate preferably has a breaking elongation of 50% or more, more preferably 100% or more, and particularly preferably 200% or more in an atmosphere of 130° C. By setting the breaking elongation to 50% or more, sufficient moldability can be expected.

[0058] If necessary, a decorative layer may be provided on the HC film. As a method for providing the decorative layer, for example, a printing method, a metal vapor deposition method, etc. may be cited. In addition, both the printing method and the metal vapor deposition method may be used for decoration. In addition, in order to further improve the adhesion between the injection molding resin and the HC film, an adhesive layer or a primer layer may be provided on the HC film.

[0059] A protective film can be attached to the HC film to protect the surface coated with the HC resin composition. By using a protective film, scratches during insert molding and overmolding can be suppressed, and the yield rate is expected to be improved.

[0060] HC film has abrasion resistance and chemical resistance, high elongation at break, good formability, and excellent weather resistance. Therefore, HC film is suitable as a material for insert molded products and molded products for outdoor use. Examples of insert molded products and molded products for outdoor use include insert molded products and molded products for automobile exteriors.

[0061] 3. Insert molding and out-molded products

[0062] As a method of using HC film in insert molding, the following method can be cited. First, the HC film is arranged in a mold. At this time, it is arranged so that the surface coated with the HC resin composition faces the inner wall surface of the mold (that is, the surface opposite to the solidified layer of the HC resin composition is in contact with the molding resin). If necessary, the HC film can be pre-molded according to the shape of the mold. Next, the mold is closed, and the molding resin in a molten state is injected into the mold cavity, and the insert molded product is formed by solidifying the resin.

[0063] As methods for performing the above-mentioned pre-molding, the following methods can be cited: a method of preheating the HC film to a temperature above its softening point and then placing it in a mold, and performing vacuuming through a suction hole provided on the mold; or using a molding mold different from the injection molding mold and adopting a known molding method such as vacuum molding, pressure molding, and stamping molding. In addition, it is also possible to perform molding simultaneously and integrally with the injection resin by using the injection pressure of the molding resin without performing the above-mentioned pre-molding.

[0064] As the injection molding resin, a known resin capable of injection molding can be used. As the injection molding resin, for example, polyethylene resin, polypropylene resin, polystyrene resin, ABS resin, AS resin, acrylic resin, polyurethane resin, polyester resin, polycarbonate resin, polyphenylene ether resin, polyacetal resin, polysulfone resin, etc. can be listed. As the injection molding resin, it can be used alone or in combination of two or more. In the case of a large size such as an automobile body, or even in the case of a small size but a thin wall thickness, by making the shrinkage rate of the injection molding resin after molding close to the shrinkage rate of the HC film, the occurrence of defects such as warping can be suppressed.

[0065] Furthermore, by coloring the injection molding resin, the decorative layer of the HC film can be omitted. In addition, the injection molding resin can be colored so that the color of the decorative layer blends with the color of the injection molding resin. In this case, the insert molding can have a darker appearance.

[0066] Insert molded products can be used instead of products with exterior coloring by paint. Examples of products with exterior coloring by paint include automobile bodies. By coloring the injection molding resin, the exterior painting of insert molded products using paint can be omitted. Appearance defects such as orange peel and pits often appear during exterior painting. If exterior painting is omitted, insert molded products are less likely to have appearance defects.

[0067] HC film can also be used for OOM. For example, HC film can be used for TOM (Three-Dimensional Overlay Method) molding. TOM molding is a film molding method that uses vacuum / pressure molding in a closed box to create three-dimensional surface decoration on a preformed substrate. By using HC film for OOM, large three-dimensional products can be manufactured regardless of the substrate material.

[0068] 4. Examples

[0069] Hereinafter, the present disclosure will be described in detail by citing examples and comparative examples, but the examples are used to illustrate specific examples and are not limited to the examples. In addition, unless the measurement conditions are described, the measurement is performed under the conditions of 25° C. and a relative humidity of 65%. In addition, the blending amount refers to the weight part converted to the solid content.

[0070] (4-1) Preparation of Ure Ac

[0071] (i) Preparation of Ure Ac1

[0072] In a four-necked flask equipped with a stirrer, a reflux condenser, a dropping funnel and a thermometer, 200 parts by weight of ethylene glycol, 825 parts by weight of IPDI (NCO content of 37.5%), a catalyst and MEK were added to prepare a mixture with a solid content of 50%, and then stirred for reaction at 80°C for 6 hours. When it was confirmed by infrared absorption analysis that the peak value of the isocyanate group reached the specified amount, the reaction was terminated.

[0073] Next, 438 parts by weight of PETA (hydroxyl value of 120 mgKOH / g) was added, stirred and reacted at 70°C for 6 hours, and then infrared absorption analysis was performed to confirm that the isocyanate group disappeared. Next, MEK was used to adjust the solid content to 50%. Through the above steps, hexafunctional Ure Ac1 with a Mw of 6,200 was obtained. Ure Ac refers to polyurethane acrylate.

[0074] (ii) Preparation of Ure Ac2

[0075] In a four-necked flask equipped with a stirrer, a reflux condenser, a dropping funnel and a thermometer, 200 parts by weight of ethylene glycol, 930 parts by weight of IPDI (NCO content of 37.5%), a catalyst and MEK were added to prepare a mixture with a solid content of 50%, and then the mixture was stirred and reacted at 80°C for 6 hours. When it was confirmed by infrared absorption analysis that the peak value of the isocyanate group reached the specified amount, the reaction was terminated.

[0076] Next, 886 parts by weight of PETA (hydroxyl value 120 mgKOH / g) was added, stirred and reacted at 70°C for 6 hours, and then infrared absorption analysis was performed to confirm that the isocyanate group disappeared. Next, MEK was used to adjust the solid content to 50%. Through the above steps, hexafunctional Ure Ac2 with a Mw of 3,200 was obtained.

[0077] (iii) Preparation of Ure Ac3

[0078] In a four-necked flask equipped with a stirrer, a reflux condenser, a dropping funnel and a thermometer, 200 parts by weight of ethylene glycol, 895 parts by weight of IPDI (NCO content of 37.5%), a catalyst and MEK were added to prepare a mixture with a solid content of 50%, and then stirred for reaction at 80°C for 6 hours. When it was confirmed by infrared absorption analysis that the peak value of the isocyanate group reached the specified amount, the reaction was terminated.

[0079] Next, 743 parts by weight of PETA (hydroxyl value: 120 mgKOH / g) was added, stirred and reacted at 70°C for 6 hours, and then infrared absorption analysis was performed to confirm that the isocyanate group disappeared. Next, MEK was used to adjust the solid content to 50%. Through the above steps, hexafunctional Ure Ac3 with a Mw of 3,800 was obtained.

[0080] (iv) Preparation of Ure Ac4

[0081] In a four-necked flask equipped with a stirrer, a reflux condenser, a dropping funnel and a thermometer, 200 parts by weight of ethylene glycol, 808 parts by weight of IPDI (NCO content of 37.5%), a catalyst and MEK were added to prepare a mixture with a solid content of 50%, and then stirred for reaction at 80°C for 6 hours. When it was confirmed by infrared absorption analysis that the peak value of the isocyanate group reached the specified amount, the reaction was terminated.

[0082] Next, 371 parts by weight of PETA (hydroxyl value: 120 mgKOH / g) was added, stirred and reacted at 70°C for 6 hours, and then infrared absorption analysis was performed to confirm that the isocyanate group disappeared. Next, MEK was used to adjust the solid content to 50%. Through the above steps, hexafunctional Ure Ac4 with a Mw of 7,800 was obtained.

[0083] (v) Preparation of Ure Ac5

[0084] In a four-necked flask equipped with a stirrer, a reflux condenser, a dropping funnel and a thermometer, 200 parts by weight of ethylene glycol, 790 parts by weight of IPDI (NCO content of 37.5%), a catalyst and MEK were added to prepare a mixture with a solid content of 50%, and then the mixture was stirred and reacted at 80°C for 6 hours. When it was confirmed by infrared absorption analysis that the peak value of the isocyanate group reached the specified amount, the reaction was terminated.

[0085] Next, 295 parts by weight of PETA (hydroxyl value 120 mgKOH / g) was added, stirred and reacted at 70°C for 6 hours, and then infrared absorption analysis was performed to confirm that the isocyanate group disappeared. Next, MEK was used to adjust the solid content to 50%. Through the above steps, hexafunctional Ure Ac5 with a Mw of 9,800 was obtained.

[0086] (vi) Preparation of Ure Ac A to C

[0087] Ure Ac A and Ure Ac B having the same skeleton as Ure Ac 1 to 5 were prepared by the same preparation method as Ure Ac 1 to 5, but adjusting the Mw. Ure Ac C was prepared by the same preparation method as Ure Ac 1 to 5, but replacing ethylene glycol with polyethylene glycol. The specific contents of Ure Ac A to C are shown below.

[0088] Ure Ac A: PETA-IPDI-(ethylene glycol-IPDI)n-PETA skeleton, six functional groups, solid content 50%, Mw 1,800.

[0089] Ure Ac B: PETA-IPDI-(ethylene glycol-IPDI)n-PETA skeleton, six functional groups, solid content 50%, Mw 13,000.

[0090] Ure Ac C: PETA-IPDI-polyethylene glycol-IPDI-PETA backbone, hexafunctional group, solid content 50%, Mw 6,000.

[0091] (4-2) Production of HC resin composition

[0092] The components listed in Table 1 were mixed according to the amounts listed in Table 1 and stirred until they were uniformly dissolved and dispersed, and then PGM was added to dilute and stirred until the solid content reached 30%, thereby preparing HC resin compositions of Examples 1 to 9 and Comparative Examples 1 to 3.

[0093] In addition, the components listed in Table 2 were mixed in the amounts listed in Table 2 and stirred until they were uniformly dissolved and dispersed, and then PGM was added to dilute and stirred until the solid content reached 30%, thereby preparing HC resin compositions of Comparative Examples 4 and 5.

[0094] [Table 1]

[0095]

[0096] [Table 2]

[0097]

[0098] In Table 1 and Table 2, (A) is Ure Ac 1 to 5. (b1) is Tinuvin 249 (trade name, manufactured by BASF Japan). (b2) is Tinuvin 477 (trade name, manufactured by BASF Japan). (C) is Omnirad 2959 and 127D (trade name, manufactured by IGM Resins). The crosslinking agent is DPHA.

[0099] The additives are X-71-1203M (trade name, manufactured by Shin-Etsu Chemical Co., Ltd., an acryl-containing fluorine-containing organic silicon compound) and BYK-UV3500 (trade name, manufactured by BYK, a polydimethylsiloxane copolymer compound). X-71-1203M is a leveling agent.

[0100] (4-3) Evaluation method of HC resin composition

[0101] The HC resin composition of each example and each comparative example was evaluated by the following method.

[0102] (i) Preparation of HC film for evaluation

[0103] As a substrate, a UPILON film DF02PUL (trade name, manufactured by Mitsubishi Gas Chemical Co., Ltd.) was prepared. This substrate is a PMMA / PC laminate film and has a thickness of 125 μm.

[0104] The HC resin composition was applied to one side of the PMMA layer of the substrate to form an HC resin composition layer. The dry film thickness of the HC resin composition layer was 3 μm. Next, the HC resin composition layer was dried in a thermostatic bath at 80° C. for 1 minute. Next, the HC resin composition layer was irradiated with ultraviolet light using a high-pressure mercury lamp in a nitrogen atmosphere to obtain an HC film for evaluation. The output power of the high-pressure mercury lamp was 1300 mW / cm2. The cumulative light amount of ultraviolet light was 200 mJ.

[0105] (ii) Evaluation of curability

[0106] The coating surface of the HC resin composition in the evaluation HC film (hereinafter referred to as the coating surface) was touched with a finger to determine whether there was tackiness. The curability of the HC resin composition layer was evaluated based on the following criteria. ○ indicates that the evaluation result is better than ×.

[0107] ○: No stickiness.

[0108] ×: Sticky.

[0109] (iii) Evaluation of fit

[0110] The adhesion was evaluated by the cross-cut test method of JIS K 5600-5-6. A cutting tool was used to form a grid-like cut on the coated surface of the HC film for evaluation. The grid had 10×10 squares. The spacing between the cuts was 1 mm.

[0111] Next, a cellophane tape CT-24 (trade name, manufactured by Nichiban Corporation) was attached to the cut portion, and the cellophane tape was pulled upward. The peeling condition of the HC resin composition layer was confirmed. The adhesion of the HC resin composition layer was evaluated according to the following criteria.

[0112] O: There is no square in which the HC resin composition layer peeled off among 100 squares.

[0113] ×: One or more HC resin composition layers peeled off among 100 squares.

[0114] (iv) Wear resistance evaluation

[0115] The wear resistance was evaluated using a friction tester FR-IBS manufactured by Suga Testing Machine Co., Ltd. A white cotton cloth (Kanakin No. 3) for testing was installed on a friction element with a diameter of 16 mm. The friction element was brought into contact with the coated surface of the evaluation HC film under a load of 9N. The friction element was reciprocated 20 times at a speed of 1 reciprocation / second. The distance of one reciprocation was 100 mm. After 20 reciprocations, the coated surface of the evaluation HC film was observed, and the wear resistance of the HC resin composition layer was evaluated according to the following standards.

[0116] ○: No scratches.

[0117] ×: There are scratches.

[0118] (v) Chemical resistance evaluation

[0119] Hand cream was applied to the coated surface of the HC film for evaluation and left at 80°C for 4 hours. The hand cream was Neutrogena SPF45 (trade name, manufactured by Johnson & Johnson). Next, the temperature of the HC film for evaluation was returned to room temperature and the hand cream was wiped off. The surface of the wiped-off hand cream was observed, and the chemical resistance of the HC resin composition layer was evaluated according to the following criteria.

[0120] ○: There is no trace of hand cream applied.

[0121] ×: There are traces of hand cream applied.

[0122] (vi) Evaluation of elongation at break

[0123] The HC film for evaluation was cut into a rectangle with a width of 25 mm and a length of 110 mm to prepare a test piece. The test piece was subjected to a tensile test at an ambient temperature of 130° C. and a tensile speed of 300 mm / min using TechnoGraph TGI-1KN manufactured by Minebea. In the tensile test, the distance between the chucks was 50 mm. During the tensile test, the test piece was visually checked for cracks. The elongation at break X (%) was calculated using the following mathematical formula (1).

[0124] Mathematical formula (1) X = (A / 50) × 100

[0125] In the mathematical formula (1), A is the elongation of the specimen when it breaks (mm). Since the chuck spacing is 50 mm, A is the elongation of the specimen per 50 mm.

[0126] The elongation at break of the evaluation HC film was evaluated according to the following criteria: ◎ indicates a better evaluation result than 0.

[0127] ◎: The elongation at break is 200% or more.

[0128] O: The elongation at break is 50% or more and less than 200%.

[0129] ×: The elongation at break is less than 50%.

[0130] (4-4) Evaluation results of HC resin composition

[0131] Tables 3 and 4 show the evaluation results of the HC resin compositions.

[0132] [Table 3]

[0133]

[0134] [Table 4]

[0135]

[0136] The HC resin composition of each example has good evaluation results in terms of curability, adhesion, wear resistance, chemical resistance and elongation at break.

[0137] Comparative Example 1, which contains Ure Ac A with a small Mw, has a low elongation at break. Comparative Example 2, which contains Ure Ac B with a large Mw, has poor wear resistance. Comparative Example 3, which contains Ure Ac having a polyethylene skeleton, has poor chemical resistance. Comparative Example 4 does not contain X-71-1203M, and its wear resistance is poor. Comparative Example 5 uses BYK-UV3500 instead of X-71-1203M, and when a film for molding is manufactured using it, the weather resistance of the film for molding is poor. This will be shown in the evaluation of the HC film described later.

[0138] (4-5) Preparation of HC film

[0139] HC films S1 to S13 were prepared using the HC resin compositions and substrates shown in Table 5 or Table 6.

[0140] [Table 5]

[0141]

[0142] [Table 6]

[0143]

[0144] "WAT" in Table 5 refers to Wavelock Advanced Technology. "HC Resin" in Tables 5 and 6 refers to HC resin composition. "Component" in Tables 5 and 6 refers to the component of the substrate. "Manufacturer" in Tables 5 and 6 refers to the manufacturer of the substrate. "PMMA / PC" in Tables 5 and 6 refers to PC / acrylic composite substrate.

[0145] The manufacturing method of HC films S1 to S13 is as follows. The HC resin composition is applied to the surface of one side of the substrate, thereby forming an HC resin composition layer. When the component of the substrate is a PC / acrylic composite substrate, the HC resin composition is applied to one side of the PMMA layer, thereby forming an HC resin composition layer. However, in S10 to S11, the HC resin composition is not applied to the substrate.

[0146] The dry film thickness of the HC resin composition layer was 3 μm. Next, the HC resin composition layer was dried in a thermostatic chamber at 80° C. for 1 minute. Next, the HC resin composition layer was irradiated with ultraviolet light using a high-pressure mercury lamp in a nitrogen atmosphere, thereby obtaining an HC film. The output power of the high-pressure mercury lamp was 1300 mW / cm2. The cumulative light amount of ultraviolet light was 200 mJ.

[0147] (4-6) Evaluation method of HC film

[0148] The HC films S1 to S13 were evaluated by the following method.

[0149] (i) ΔE of the substrate alone

[0150] The ΔE of the substrate alone not coated with the HC resin composition was measured. The method for measuring ΔE was based on JIS Z 8722. The ΔE was measured using a colorimeter SD-6000 manufactured by Nippon Denshoku Industries Co., Ltd. The specific method for measuring ΔE was as follows.

[0151] Before UVB was irradiated to the substrate monomer, the color appearance of the substrate monomer was measured. Next, the substrate monomer was irradiated with UVB at 60°C for 1000 hours. The UVB intensity was 0.55 W / m2. Next, the color appearance of the substrate monomer was measured again. The difference between the color appearance of the substrate monomer before UVB irradiation and the color appearance of the substrate monomer after UVB irradiation was taken as the ΔE of the substrate monomer.

[0152] (ii) Weather resistance

[0153] The ΔE of the HC film was measured in the same manner as the ΔE of the substrate alone. The weather resistance of the HC film was evaluated according to the following criteria.

[0154] ○: ΔE of the HC film is less than 1.0.

[0155] ×: ΔE of the HC film exceeds 1.0.

[0156] (iii) Formability

[0157] The HC film was heated until the temperature of the substrate reached 180° C. Next, the HC film was vacuum-formed in a vacuum forming machine using a cylindrical mold having a diameter of 30 mm and a height of 4 mm. The formability of the HC film was evaluated according to the following criteria.

[0158] O: Can be fully formed.

[0159] ×: Whitening or cracking occurs, or molding is incomplete.

[0160] (iv) Cloth mark test

[0161] A 50mm x 50mm gauze was placed in contact with the coated surface of the HC film under a load of 500Kg / 4cm2. The gauze was placed at 80°C for 60 minutes under the applied load. Next, the gauze was removed from the coated surface and the coated surface was observed. The results of the cloth mark test were evaluated according to the following standards.

[0162] ○: No trace of cloth remains on the coated surface.

[0163] ×: Cloth marks remain on the coated surface.

[0164] (v) Wear resistance

[0165] The wear resistance was evaluated using a friction tester FR-IBS manufactured by Suga Testing Machine Co., Ltd. A white cotton cloth (Kanakin No. 3) for testing was installed on a friction element with a diameter of 16 mm. The friction element was brought into contact with the coated surface of the HC film under a load of 1 kg / cm2. The friction element was reciprocated 20 times at a speed of 1 reciprocation / second. The distance of one reciprocation was 100 mm. After 20 reciprocations, the coated surface of the HC film was observed, and the wear resistance of the HC film was evaluated according to the following standards.

[0166] O: No scratches.

[0167] ×: There are scratches.

[0168] (vi) Pencil hardness

[0169] The pencil hardness of the coated surface of the HC film was measured under a load of 500 g using a pencil scratch coating hardness tester (P type) manufactured by Toyo Seiki Seisaku-sho, Ltd. in accordance with JIS K5600-5-4 (1999 edition). The pencil hardness measurement results were evaluated according to the following criteria.

[0170] O: Pencil hardness is H or higher.

[0171] ×: Pencil hardness is F or less.

[0172] (4-7) Evaluation results of HC films

[0173] The evaluation results of the HC films are shown in Tables 7 and 8.

[0174] [Table 7]

[0175]

[0176] [Table 8]

[0177]

[0178] S1 to S3 have good evaluation results in various aspects such as weather resistance, formability, cloth mark test, abrasion resistance, and pencil hardness.

[0179] On the other hand, S4 to S6 using PMMA / PC substrates with a ΔE of the substrate alone greater than 1.0 had poorer weather resistance evaluation results than S1 to S3. In addition, S7 using a PC substrate had poorer evaluation results in terms of weather resistance and pencil hardness than S1 to S3.

[0180] In addition, S8 using an acrylic resin substrate had poorer evaluation results in terms of cloth mark test and pencil hardness than S1 to S3. In addition, S9 using a PET substrate had poorer evaluation results in terms of weather resistance and moldability than S1 to S3.

[0181] In addition, S10 to S11 without HC resin composition coating had poor evaluation results in abrasion resistance and pencil hardness. In addition, S11 also had poor evaluation results in weather resistance. In addition, S12, whose HC resin composition was Comparative Example 4, had poor evaluation results in abrasion resistance. In addition, S13, whose HC resin composition was Comparative Example 5, had poor evaluation results in weather resistance.

[0182] (4-8) Evaluation of injection molding

[0183] Insert molding was performed using HC film S1 to produce insert molded products. The injection molded resin was black ABS. WaveScan3Dual, a coating surface property measuring machine manufactured by BYK, was used to measure LW (long wave) and SW (short wave) on the film surface of the insert molded product. In addition, the same measurement was performed on the painted surface of the coated steel plate as a comparison object. The measurement results are shown in Table 9. In addition, the appearance of the film surface of the insert molded product and the painted surface of the coated steel plate were observed and evaluated. The evaluation results are shown in Table 9.

[0184] [Table 9]

[0185]

[0186] The film surface of the insert molded product has no appearance defects caused by orange peel. On the other hand, the painted surface of the painted steel sheet has appearance defects caused by orange peel.

[0187] 5. Other Implementation Methods

[0188] Although the embodiments of the present disclosure have been described above, the present disclosure is not limited to the above embodiments and can be implemented in various modified forms.

[0189] (5-1) The functions of one constituent element in the above-mentioned embodiment may be dispersed and arranged in a plurality of constituent elements, or the functions of a plurality of constituent elements may be integrated into one constituent element. In addition, a part of the structure of the above-mentioned embodiment may be omitted. In addition, at least a part of the structure of the above-mentioned embodiment may be added to the structure of the other embodiments, or at least a part of the structure of the above-mentioned embodiment may be replaced with the structure of the other embodiments.

[0190] (5-2) The present disclosure can be implemented in various forms other than the above-mentioned HC resin composition, such as a product containing the HC resin composition as a component and a method for producing the HC resin composition.

Claims

1. A hard coating resin composition for a film for molding an automobile exterior, characterized in that: Include: Polyurethane acrylate (A), a light stabilizer (B), a photopolymerization initiator (C), and a fluorine-containing organosilicon compound having a reactive functional group, wherein (A) has a structure formed by further reacting a diisocyanate generated by the reaction of ethylene glycol and isophorone diisocyanate with pentaerythritol triacrylate, and the weight average molecular weight of (A) is 3,500 to 12,000.

2. The hard-coat resin composition for a film for molding an automobile exterior according to claim 1, characterized in that: The (B) contains a radical scavenger (b1) and an ultraviolet absorber (b2), The amount of (b1) blended is 1 to 10% by weight relative to the total solid content, and the amount of (b2) blended is 0.3 to 5% by weight relative to the total solid content.

3. The hard-coat resin composition for a film for molding an automobile exterior according to claim 1, characterized in that The blending amount of the fluorine-containing organosilicon compound having a reactive functional group is 0.1 to 3% by weight based on the total solid content.

4. A hard coating film for molding, characterized in that have: Base material; as well as A cured layer of the hard-coat resin composition for a film for molding automobile exterior according to any one of claims 1 to 3 formed on the substrate.

5. The hard coating film for molding according to claim 4, characterized in that The substrate is a composite substrate comprising a polycarbonate substrate and an acrylic substrate. The strength at 60°C is 0.55W / m 2 The ΔE of the composite substrate before and after 100 hours of UVB irradiation is 1.0 or less.

6. A method for manufacturing an insert molded product, characterized in that: Using a mold, a hard coating film for molding having a substrate and a cured layer on the substrate is molded, The molten resin is injected from the side opposite to the solidified layer to form a resin molded product. The cured layer is a cured product of a resin composition, which comprises: Polyurethane acrylate (A), a light stabilizer (B), a photopolymerization initiator (C), and a fluorine-containing organosilicon compound having a reactive functional group, wherein (A) has a structure formed by further reacting a diisocyanate generated by the reaction of ethylene glycol and isophorone diisocyanate with pentaerythritol triacrylate, and the weight average molecular weight of (A) is 3,500 to 12,000.

7. The method for manufacturing an insert molded product according to claim 6, wherein: The molten resin is colored.

8. An insert molded product, characterized in that: The hard coating film for molding according to claim 4 is used.

9. An out-of-mold molded product, characterized in that The hard coating film for molding according to claim 4 is used.

Citation Information

Patent Citations

  • JP1973048200A

  • Manufacturing method of light-emitting element and extracting method of hydrogen from light-emitting element

    JP2022110973A